ANALISIS TEGANGAN PRINSIPAL PADA CHASSIS MOBIL LISTRIK TIPE PROTOTYPE - Santoso Mulyadi; Muh Nurkoyim Kustanto; Cahya Alief Prasetyo; Gaguk Jatisukamto; Rika Dwi Hidayatul Qoryah; Yuni Hermawan; Mahros Darsin (POLITALA PRESS, 2022)
An electric car is a vehicle that is driven by an electric motor, the electric motor obtains power from electricity stored in the battery. Chassis is an important component in electric cars. Chassis is part of an electric car that functions as a support system in an electric car. In the chassis there is a maximum and minimum stress called the principal stress. This principal stress becomes a reference to determine the safety of the chassis. So it is necessary to know the principal stress on the chassis. The testing process uses two drivers, each of which weighs 45 kg and 56 kg. The tests were carried out at three different points on the electric car chassis. From the results of the principal stress test, Ïƒ1 = 3.3282 MPa and Ïƒ2 = 1.5429 MPa for the 45 kg driver and Ïƒ1 = 3.8233 MPa and Ïƒ2 = 2.1123 MPa for the 56 kg driver. The principal stress on the chassis is still in a safe condition because it does not exceed the yield stress of the chassis material.